FUNGSI BADAN PERMUSYAWARATAN DESA MARSAWA KECAMATAN SENTAJO RAYA KABUPATEN KUANTAN SINGINGI TAHUN 2023 - Marsa, Lilis Tri; Zebua, Ben Hansel Notatema (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
Based on Regulation of the Minister of Home Affairs of the Republic of Indonesia Number 110 of 2016 concerning Village Consultative Bodies, the Village Consultative Bodies (BPD) have important functions and duties in the village government system. The BPD's functions include discussing and agreeing on draft village regulations with the village head, accommodating and channeling community aspirations, and overseeing the village head's performance. These functions are carried out, among other things, to meet community needs, including development. This study aims to determine the implementation of the functions of the Village Consultative Body (BPD) of Marsawa Village in road construction in Marsawa Village, Sentajo Raya District, Kuantan Singingi Regency in 2023. This study uses a qualitative research method with a qualitative descriptive type of research. The theory used for this study uses the theory of Deliberative Democracy to see the extent of the implementation of the BPD's functions. Research results indicate that the function of the Village Consultative Body (BPD) in accommodating and channeling the aspirations of the community has been operating well through citizen dialogue sessions in each hamlet as a participatory forum, especially concerning road infrastructure needs. The BPD's function in discussing and approving draft village regulations is also carried out through the Musrenbang forum, where the BPD acts as a representative institution of the residents. However, decisions are still dominated by the executive, so some aspirations have not been accommodated. The supervisory function over the village head's performance is carried out through dialogue and deliberative meetings, although some programs, such as road construction, have not been realized due to funding limitations and cross-government coordination issues. Keywords: BPD, Function, Supervision